Genre et discours pénal : la bigamie dans la doctrine juridique européenne de l’époque moderne (XVI-XVIIIe siècle) - Tanguy Le Marc’hadour (Criminocorpus)
This study attempts to trace the evolution of European criminal doctrine (Italy, Spain, Germany, the Netherlands, France) from the sixteenth to the eighteenth centuries in relation to the crime of bigamy, which seemed relevant for a study of legal discourse from a gender perspective. The legal existence of the crime of bigamy, hitherto little studied, depends mainly on doctrinal writings, and the study seeks to identify the differences in the discourse concerning men and women. It shows that the two different criminal qualifications for women and men found in the Roman texts were transformed by doctrine into a single, sexually undifferentiated offence in the modern period, while paradoxically maintaining a gendered apprehension in the degree of repression, in accordance with the expected social roles of women and men.